How is the Mathematical Connection Ability of Post-Pandemic Class IV Elementary School Students in whole Numbers Material? - Nabillah, Rokhmatun; Herwin, Herwin; Tandukar, Kritika (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to analyze the mathematical connection ability of elementary school students in the material as whole counting numbers, and categories and based on indicators of mathematical connection ability. The subjects were students from Class IV as many as 114 elementary school students. This research is qualitative descriptive research using a purposive sampling technique. The research instruments used were a mathematical connection ability test and an interview. The indicators of the ability of mathematical connections measured include the relationship of mathematics with mathematics, the relationship of mathematics with other sciences, and the relationship of mathematics with everyday life. The results showed: (1) an overall mathematical connection ability of 24% including the category of less; (2) based on the category of mathematical connection ability showed that 49% of students are very less, 37% less Category, 7% Category enough, 7% Good category and 0% very good category; (3) the ability of mathematical connections based on indicators a) the relationship of mathematics with mathematics by 18% (very less Category), b) the relationship of mathematics with other sciences by 35% (less category), and c) the relationship of mathematics with everyday life by 17% (very less category). This shows that the ability of mathematical connections is still not owned by the fourth-grade students of elementary school and requires attention and further development by teachers and the school. Penelitian ini bertujuan unruk menganalisis kemampuan koneksi matematis siswa sekolah dasar pada materi bilangan cacah secara keseluruhan, kategori dan berdasarkan indikator kemampuan koneksi matematis. Subjek penelitian adalah siswa dari kelas IV sebanyak 114 siswa sekolah dasar. Penelitian ini merupakan jenis penelitian deskriptif kualitatif dengan menggunakan teknik purposive sampling. Instrumen penelitian yang digunakan adalah tes kemampuan koneksi matematis dan wawancara. Indikator kemampuan koneksi matematis yang diukur meliputi: hubungan matematika dengan matematika, hubungan matematika dengan ilmu lain dan hubungan matematika dengan kehidupan sehari-hari. Hasil penelitian menunjukan: (1) secara keseluruhan kemampuan koneksi matematis sebesar 24% termasuk kategori kurang; (2) berdasararkan kategori kemampuan koneksi matematis menunjukan bahwa 49% siswa berkemampuan sangat kurang, 37% kategori kurang, 7% kategori cukup, 7% kategori baik dan 0% kategori sangat baik; (3) Kemampuan koneksi matematis berdasarkan indikator a) hubungan matematika dengan matematika sebesar 18% (kategori sangat kurang), b) hubungan matematika dengan ilmu lain sebesar 35% (kategori kurang), dan c) hubungan matematika dengan kehidupan sehari-hari sebesar 17% (kategori sangat kurang). Hal ini menunjukan bahwa kemampuan koneksi matematis masih belum dimiliki oleh siswa kelas IV sekolah dasar dan memerlukan perhatian serta pengembangan lebih lanjut oleh guru maupun pemangku kebijakan lainnya.